2013
DOI: 10.1021/jp409481f
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Ion Interactions with Aqueous Glucose: Insights from Quantum Mechanics, Molecular Dynamics, and Experiment

Abstract: In the last several decades, significant efforts have been conducted to understand the fundamental reactivity of glucose derived from plant biomass in various chemical environments for conversion to renewable fuels and chemicals. For reactions of glucose in water, it is known that inorganic salts naturally present in biomass alter the product distribution in various deconstruction processes. However, the molecular-level interactions of alkali metal ions and glucose are unknown. These interactions are of physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 84 publications
(160 reference statements)
2
47
0
Order By: Relevance
“…30 Moreover, Patwardhan et al, 11 and other researchers 40,41 reported that the cations had a much greater effect on the product distribution of fast pyrolysis of cellulose than the anions did. With NaCl present in fast pyrolysis of glucose-based carbohydrates at 500 8C in this study, chloride would be efficiently volatilized while sodium would stay in the melt phase, based on the experimental findings from the literature.…”
Section: Mechanistic Modeling Of the Effects Of Nacl On Fast Pyrolysismentioning
confidence: 96%
See 2 more Smart Citations
“…30 Moreover, Patwardhan et al, 11 and other researchers 40,41 reported that the cations had a much greater effect on the product distribution of fast pyrolysis of cellulose than the anions did. With NaCl present in fast pyrolysis of glucose-based carbohydrates at 500 8C in this study, chloride would be efficiently volatilized while sodium would stay in the melt phase, based on the experimental findings from the literature.…”
Section: Mechanistic Modeling Of the Effects Of Nacl On Fast Pyrolysismentioning
confidence: 96%
“…14,21,22 Furthermore, Na 1 would be likely to bind with oxygen atoms in the reactive species. 26,[28][29][30] In this work, Na 1 ions were assumed to be able to bind with all the neutral species including polymeric chains and LMW species and form Na 1 -complex species (Na 1 -complexes). Once these complexes are formed, they can undergo the same reactions as their neutral counterparts, but with different kinetics.…”
Section: Mechanistic Modeling Of the Effects Of Nacl On Fast Pyrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…20,56,57 Several previous studies have found that the cation of an inorganic salt such as NaCl interacts more closely with carbohydrates than do anions such as Cl − , 47,58,59 justifying continued focus on the effects of the cation on carbohydrate pyrolysis reactions. Our previous simulation work indicates that cations directly interact with the nucleophilic oxygens, 58 which are central in the dominant reactions in carbohydrate pyrolysis, dehydration, and isomerization. [23][24][25]29,30 In contrast, the counterion, Cl − , was preferably located farther from the carbohydrate reaction centers, interacting instead with the partially positively charged hydrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its theoretical importance, the study is of biological or physiological interests as well, for example, its possible relation to cation-monosaccharide co-transport [45,46].…”
Section: Introductionmentioning
confidence: 99%